An experimental study of triggers and needs of threats in critical adversity situations in a student sample - Rynek, Mona; Ellwart, Thomas (Frontiers in Psychology, 2022)
Emergency teams facing critical adversity situations (CAS) often feel questioned in their professional roles as conscientious rescuers, leading to feelings of threats as a kind of stress experience. According to the stress-as-offence-to-self theory (Semmer et al., 2007), perceptions of insufficiency and disrespect trigger threats by frustrating underlying needs. In this study, we explored threats in the context of a CAS by analysing the direct and future-related consequences of threats, investigating the activation of threat triggers during the action and postaction phases of teamwork, and evaluating the mediating role of needs. In a multitask experiment, teams (N = 60 dyads) experienced a controllable mission (non-CAS), followed by a CAS mission in a computer simulation task. After the CAS, teams received negative feedback (situation-nonspecific feedback; situation-specific feedback; no feedback). We measured threats; the activation of insufficiency and disrespect triggers; and the frustration of needs. While insufficiency triggers were activated in the CAS but not in the non-CAS, disrespect triggers were activated by situation-nonspecific and situation-specific feedback but not by no feedback. Furthermore, the results of mediation models indicated the presence of the postulated need-based mechanism between triggers and threats. Our study highlights that the action and postaction phases of a CAS pose a variety of risks for experiencing threats. As individuals cope with these risks, needs are important mediators.